Pengaruh Kinerja Karyawan Terhadap Kepuasan, Kepercayan dan Loyalitas Konsumen (Studi Kasus pada Konsumen Hotel Elmi Surabaya) - Eko Winarni; Ni’matun Nur Rohmah (Fakultas Ekonomi Universitas Yos Soedarso, 2022)
This study aims to determine: (1) the effect of employee performance on customer satisfaction; (2) the influence of consumer satisfaction on consumer confidence; and (3) the effect of consumer trust on consumer loyalty. In this study, the variables that shape employee performance include: tangibles, reliability, responsiveness, assurance and empathy. Variables that make up consumer satisfaction, include: suitability with needs and suitability with benefits. The variables that make up consumer trust include: credibility, integrity and kindness. Variables that form consumer loyalty include: continue purchasing, say positive things and recommend friends. This type of research is a case study on consumers of Hotel Elmi Surabaya with a total sample of 140 respondents. Data collection techniques used were questionnaires and interviews conducted in January-April 2022. The sampling technique used was purposive and convenience sampling. The data analysis technique used is Percentage Analysis, Validity Test, Reliability Test and Structural Equation Modeling (SEM). The results of data analysis show that: (1) employee performance has an effect on customer satisfaction; (2) consumer satisfaction has an effect on consumer trust; (3) consumer trust has an effect on consumer loyalty.